Imaging in head and neck cancers: a review - Munjal, Manish; Munjal, Shubham; Saggar, Vanshika; Kaur, Hardeep; Arora, Vineeta; Sandhu, Lovleen; Bharadwaj, Iti; Arora, Anurima; Mehta, Devambika; Pillai, Anjana (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2023)
Imaging plays a vital role in the diagnosis, therapeutics-surgical or radiotherapy and prognostication of malignancies of the head and neck region. Imaging may range from simple plain radiography of the neck and the sinuses depicting mouse nibbled features of bone erosion and encroachment of air shadows, to functional imaging that analyses the metabolic status of the cancerous bed. Contrast enhancement further can delineate the vascularity of the lesion. Different imaging modalities are employed to study the various sites and sub-sites of the face and the neck to pick up the extent of infiltration into the tissues in their vicinity.